Optimizing survival and growth of inoculated biocrust-forming cyanobacteria through native plant-based habitat amelioration - Alameda-Martín, Aitor; Chamizo, Sonia; Maggioli, Lisa; Roman, Raul; Machado-de-Lima, Náthali [UNESP]; Muñoz-Rojas, Miriam; Cantón, Yolanda (Elsevier, 2024)
Low restoration success in degraded drylands has promoted research efforts towards recovery of pioneer components of these ecosystems such as biocrusts. Biocrusts can stabilize soils and improve nutrient cycling to assist vegetation establishment, but their natural recovery following a disturbance may be very slow. Soil inoculation with biocrust-forming components such as cyanobacteria is widely spread to foster biocrust formation. However, the growth of induced biocrust can be constrained under field conditions due to the harsh environmental conditions in drylands. Thus, strategies to reduce abiotic stresses have to be explored to improve cyanobacteria survival and growth. In this study, we performed an outdoor experiment to analyze the effect of plant-based ameliorating strategies in combination with cyanobacteria inoculum on biocrust formation and improvement of degraded arid soil properties. These ameliorants consisted of a plant mesh made of Macrochloa tenacissima and a Plantago ovata-based stabilizer. Application of ameliorating treatments improved cyanobacteria growth (higher chlorophyll a content, lower albedo and higher NDVI) compared to the application of cyanobacteria inoculum alone. Inoculated soils showed higher aggregate stability than non-inoculated ones, but the highest soil stability was found in the soils treated with P. ovata and was also significantly increased in the soils covered by the M. tenacissima mesh compared to uncovered soils. Both the mesh and the P. ovata stabilizer increased soil organic carbon content by up to 10% and 172%, respectively, compared to soils without habitat amelioration. Microbial community composition was similar between control and inoculated soils and between the mesh covered and uncovered soils, indicating that neither cyanobacteria inoculation nor the vegetal mesh had negative effects on the native soil community. In contrast, the soil with the P. ovata stabilizer alone displayed a different composition, with up to 95% of the bacteria's relative abundance represented by Firmicutes. This effect needs to be considered when applying this stabilizer to prevent a potential alteration of the indigenous soil microbial community. This study indicates the viability of using plant-based ameliorating strategies to optimize the establishment and growth of cyanobacteria inoculum and maximize their effects on soil properties, thus contributing to advancing in the application of nature-based solutions for the restoration of degraded dryland ecosystems.
Keywords: Environmental stress reduction; Macrochloa tenacissima; Plant mesh; Plantago ovata; Soil microbiome; Soil stabilizer